Pathogenic effects of Streptococcus oralis intestinal colonization on bladder health in mice - Natsuno Nakamura; Kota Iioka; Hirobumi Morisaki; Nobuo Okahashi; Mie Kurosawa; Haruka Fukamachi; Shohei Matsui; Takahiro Funatsu; Hirotaka Kuwata; Momoe Itsumi (Current Research in Microbial Sciences)
Streptococcus oralis, a commensal oral Streptococcus, is known as an early colonizer of the tooth surface and causes opportunistic infections, such as bacterial endocarditis. However, its pathogenicity remains unclear. This study aimed to investigate the pathogenicity of S. oralis in vivo using a mouse model. To establish S. oralis-colonized mice, germ-free mice were orally infected with S. oralis. After colonization was confirmed, these infected mice were bred, and their offspring were used as S. oralis-colonized mice. S. oralis was detected only in the intestine of these mice, which exhibited soft stools but no significant inflammation in the examined tissues. Interestingly, S. oralis-colonized mice showed higher urination frequency. Bladder tissue analysis in S. oralis-colonized mice revealed atrophy, edema, fibrosis, and epithelial denudation. RNA sequencing analysis of the bladder in S. oralis-colonized mice indicated higher expression of genes related to chronic inflammation and extracellular matrix organization, and lower expression of genes related to anti-oxidative stress. In this study, we revealed that the commensal bacterium S. oralis induces chronic inflammation and fibrosis in the bladder of mice by intestinal colonization. Hence, our findings indicate that S. oralis has the potential to affect distal tissue beyond the oral cavity, potentially possessing a pathogenic factor involved in non-bacterial cystitis. This study highlights the potential impact of S. oralis on the urinary system of mice.